Políticas de expansão do ensino superior a distância no Brasil nas primeiras décadas do século XXI: democratização do acesso ou uma das estratégias para maximização do lucro no contexto da financeirização da educação superior privada? - Peletti, Amilton Benedito (2024)
The following thesis was defended along with the Postgraduate Program in Education of the Western Paraná State University, in Cascavel’s campus, on the Educational area’s “Education, social policies and State” line of research. Starting in the 1990’s, Brazil’s Higher Education is changed mainly due to the “liberalization” of Education as a commercialized service, the Guidelines and Basis of the National Education Law (LDBEN) (9.394/1996) and its following regulations. At the beginning of the 21st century’s first decade, distance learning is effectively implemented to, allegedly, democratize Higher Education’s accessibility, which was firstly developed in public institutions, but, due to its profit potential, the Private Enterprise begins to invest in distance learning modalities, leading to, in 2005, the ingress and enrollment rates on private educational institutions outnumber the public ones’ rates and, since then, presents an excessive growth that leads to 2021’s outnumbering of the presential ingresses in private educational institutions. Therefore, the following research has as its objective the investigation of the relationship between the distance learning’s enrollment expansion, the alleged democratization of Higher Education’s accessibility and the means of ingress via the major financial/educational groups lead by their demand for maximum profitability in private higher education institutions’ financialization scenario on the first decades of the 21st century. Also, the research emphasized problematizing the referred democratization itself, which means the forms and substances in which the access to Higher Education expanded, as well as analyzing hegemonic Private Enterprise entities’ role in the mentioned process in a dialectical approach to the relationship between both Civil and Political societies and highlighting the current capital’s amplified reproduction state in the form of financialization and its probable effects on social politics’ deployment and its limits and possibilities related to the social materiality’s contradictions. Regarding the concrete totality and its historical, economical, social, political and ideological contexts of its expansion’s consolidation, we approach to a qualitative research (both documental and biographical) guided by analyses of official documents such as laws, decrees, documented views and reports presented by official government entities, as well as class entities and international organizations and investigations on scientific papers of secondary sources related to the delimitated theme. The research’s conclusion confirms the thesis of the distance learning modalities lead, especially, to private Higher Education’s oligopolization and it configures itself as a new profit capitalization method, which maximizes their rentability as their investments decrease, using the mentioned democratization as a lobby. Furthermore, it is possible to conclude that, while public institution faced reduction or stagnation of State’s investments, the private institutions of education were widely sustained by the State Fund’s resources of student loans or fiscal renounces that followed Brazil’s Ministry of Education’s programs such as “Prouni” and “Proies”, revealing a direct relationship between the destinations of the State’s Funds, oligopolies formation, the growth and accumulation xii of the ingress rate in private Higher Education and some institutions’ “specialization” on distance learning modalities.